1971
DOI: 10.1111/j.1439-0329.1971.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Der Nachweis unsichtbarer („physiologischer”) Fluor‐Immissionsschädigungen an Waldbäumen durch eine einfache kolorimetrische Bestimmung der Peroxidase‐Aktivität

Abstract: The detection of hidden F‐injury of forest trees by a simple colorimetric determination of peroxidase actívity. The paper describes a simple routine method for determining colorimetrically peroxidase activity (p. a.) in foliage of forest tree species, including conifers. The effect of factors such as foliage age, F Content, external F dust, necrosis etc. on p. a. is investigated. Analyses of plants exposed at different distances to F exhalates of an aluminum plant show that with decreasing distance F content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Peroxidases were determined spectrophotometrically (Keller & Schwager, 1971). 30–150 mg of freeze‐dried, ground lichen powder were extracted in 3–7 ml of phosphate buffer (pH 7) using an ultraturrax mixer (Merck).…”
Section: Methodsmentioning
confidence: 99%
“…Peroxidases were determined spectrophotometrically (Keller & Schwager, 1971). 30–150 mg of freeze‐dried, ground lichen powder were extracted in 3–7 ml of phosphate buffer (pH 7) using an ultraturrax mixer (Merck).…”
Section: Methodsmentioning
confidence: 99%
“…Genetical differences between clones (KELLER 1976;KIELISZEWSKA-ROKICKA 1979;ECKERT et al 1982) and families (NIEMTUR 1979) may cause inconsistent responses of peroxidase to pollution stress. Seasonal, plant developmental (KELLER and SCHWAGER 1971;EsTERBAUER et al 1978;KHAN and MALHOTRA 1982), and climatic factors (JOKINEN et al 1983) can also complicate matters. Studies on the effects of controlled ozone exposures in bean and tomato plants have also concluded that peroxidase activity is too sensitive to and dependent on a number of endogenous and environmental factors to perform well as an indicator of pollution stress (ENDRESS et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of total peroxidase activity of pine needles was based on the method developed by KELLER and SCHWAGER (1972), but it was slightly modified at the Finnish Meteorological Institute. The temperature of the sample was kept stable during measurement by a cooled cell chamber.…”
Section: 2j Peroxidase Measurementsmentioning
confidence: 99%
“…It has been suggested that the changes in total peroxidase activity describe air pollution stress and thus may be used in practical air pollution monitoring (KELLER and ScHWAGER 1972;KELLER 1974) and to detect latent injuries caused by low pollution concentrations (KELLER 1981 peroxidase activity is sensitive to the internal physiological conditions ofthe plant (ENDRESS et al 1980) and to environmental factors. In addition, in conifers PO activity is genetically polymorphous, which may cause problems in the reliable separation of responses due to pollution from responses due to environmental factors, especially latent injuries (JOKINEN et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation